Influencer Network Analysis on Digital Marketing Startup development (Case Study on FNCT Management) - Rusli, Hanisa (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This research aims to analyze the extent to which FNCT Management's influencer network affects the growth of clients' businesses, as well as evaluate the impact of working with influencers on increasing clients' brand awareness. Design/Method/Approach: The research used a qualitative approach with a case study on FNCT Management. Data collection methods were conducted through in-depth interviews, online non-participatory observation, and document analysis. The purposive sample selected included 6 informants from agency management, cross-category influencers (beauty, sports, games, lifestyle), and clients. Data analysis used Miles and Huberman's interactive model with source triangulation techniques to ensure the validity of the research findings. Research Finding: The findings show that FNCT Management has great potential in utilizing influencer networks to support client growth and increase brand awareness. However, a strategy that focuses on content relevance, adaptation to technological changes, and ongoing relationship management is essential to maintain their competitive advantage in the digital marketing industry. Theoretical contribution/Originality: This research develops an understanding of the three-way relationship between agencies, influencers and clients in digital marketing, by highlighting strategic collaboration dynamics such as trust and goal alignment. It also provides new insights into the relevance of influencer content and the role of agencies in marketing strategy. Its originality lies in the focus on startups like FNCT Management, which offers a new perspective on digital marketing challenges and strategies on a dynamic scale. Practitionel/Policy implication: This research encourages agencies like FNCT Management to match influencers with client needs, provide strategic direction for relevant content, and use data analytics to monitor campaign effectiveness. In addition, building long-term relationships with influencers and ensuring transparency and ethics in collaboration can increase the success and credibility of marketing campaigns. Research limitation: This research has some limitations that need to be noted. Firstly, the research only focuses on FNCT Management as a case study, so the results may not be fully generalizable to other digital marketing agencies. Secondly, the qualitative approach used provides in-depth insights, but lacks the ability to measure quantitative impacts, such as increased revenue or ROI from influencer marketing campaigns. Thirdly, this study relies on interview and observation data, which is susceptible to subjective biases from informants and researchers. In addition, rapid changes in social media algorithms and digital trends may affect the relevance of the findings in the future. Further studies are needed to explore other contexts and integrate quantitative approaches to strengthen the validity of the findings.